Non-Watson-Crick basepairing and hydration in RNA motifs: molecular dynamics of 5S rRNA loop E - Réblová, Kamila; Spacková, Nad'a; Stefl, Richard; Csaszar, Kristina; Koca, Jaroslav; Leontis, Neocles B; Sponer, Jirí (Biophysical journal, 2003)
Explicit solvent and counterion molecular dynamics simulations have been carried out for a total of >80 ns on the bacterial and spinach chloroplast 5S rRNA Loop E motifs. The Loop E sequences form unique duplex architectures composed of seven consecutive non-Watson-Crick basepairs. The starting structure of spinach chloroplast Loop E was modeled using isostericity principles, and the simulations refined the geometries of the three non-Watson-Crick basepairs that differ from the consensus bacterial sequence. The deep groove of Loop E motifs provides unique sites for cation binding. Binding of Mg(2+) rigidifies Loop E and stabilizes its major groove at an intermediate width. In the absence of Mg(2+), the Loop E motifs show an unprecedented degree of inner-shell binding of monovalent cations that, in contrast to Mg(2+), penetrate into the most negative regions inside the deep groove. The spinach chloroplast Loop E shows a marked tendency to compress its deep groove compared with the bacterial consensus. Structures with a narrow deep groove essentially collapse around a string of Na(+) cations with long coordination times. The Loop E non-Watson-Crick basepairing is complemented by highly specific hydration sites ranging from water bridges to hydration pockets hosting 2 to 3 long-residing waters. The ordered hydration is intimately connected with RNA local conformational variations.
Keywords: Models, Molecular; denaturace nukleových kyselin; Sodium; párování bází; Spinacia oleracea; RNA, Ribosomal, 5S; Motion; RNA, Plant; hořčík; druhová specificita; Macromolecular Substances; Computer Simulation; Base Pairing; bakteriální RNA; Escherichia coli; Solvents; vazebná místa; makromolekulární látky; chybné párování bází; RNA ribozomální 5S; molekulární modely; Base Pair Mismatch; Binding Sites; rozpouštědla; pohyb těles; RNA rostlin; počítačová simulace; Nucleic Acid Denaturation; voda; sodík; konformace nukleové kyseliny; Species Specificity; Nucleic Acid Conformation; Water; RNA, Bacterial; Magnesium